Soil properties and infiltration characteristics response to successive rotations of production Eucalyptus plantations in headwater catchments of Phu Tho province, Vietnam - Bui Xuan Dung; Kieu Thi Duong; Phung Van Khoa; Trieu Duc Tri; Nguyen Hung Thinh (Journal of Forestry Science and Technology, 2025)
This study investigates the responses of soil properties and infiltration characteristics to successive rotations of production Eucalyptus plantations in headwater catchments of Phu Tho province, Vietnam. Fifteen plots (500 m² each), representing five rotation cycles (from first to fifth) and a natural forest control, were established. Soil physical properties (hardness, dry bulk density, porosity), chemical properties (pH, total organic carbon, total nitrogen, phosphorus, potassium), and infiltration dynamics (measured using double ring infiltrometer over 120 minutes) were assessed following Vietnamese national standards (TCVN). Results show a progressive increase in soil compaction across rotations: penetration depth declined from 9 mm in the first rotation to 4 mm in the fifth rotation, and porosity decreased from 38.13% to 28.95%, compared with 46.72% in natural forest control. Chemical fertility also decreased: total organic carbon fell by 39% (from 1.55% to 0.94%), total nitrogen by 33% (from 0.18% to 0.12%), phosphorus by 45%, and potassium by 62% across rotations, while pH declined from 3.61 to 3.26 (natural forest pH 3.71). Infiltration rates followed the same trends, with the average 5 minute rate dropping from 72 mm in the first rotation to 33 mm in the fifth, and the cumulative infiltration over 120 minute decreasied from 1,808 mm to 812 mm (natural forest: 2,065 mm). These findings demonstrate that successive Eucalyptus rotations without restorative interventions significantly degrade soil structure, nutrient status, and hydrological function.